2022
DOI: 10.1177/20503121221094178
|View full text |Cite
|
Sign up to set email alerts
|

Male involvement in family planning use and associated factors among currently married men in rural Eastern Ethiopia

Abstract: Introduction/Objectives: Male involvement in family planning refers to all organizational actions focused on men as a distinct group to increase the acceptability and uptake of family planning among either sex. Despite the growing evidence of male involvement in increasing family planning uptake among couples, a little success has been achieved in Ethiopia, especially in rural areas. Hence, this study aimed to assess male involvement in family planning and its associated factors among currently married men in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…It is now necessary to actively encourage fathers and male community members to help care for women and support their family in receiving adequate and improved healthcare. There is a positive correlation between male participation in family planning decisions and improved maternal and child health outcomes, according to a number of studies [ 80 , 81 ]. To achieve universal access to reproductive health care services, as part of the 2030 Agenda for Sustainable Development, it is crucial to increase access to contraception and ensure that the demand for FP is satisfied when utilizing effective contraceptive methods.…”
Section: Male Involvement In Family Planning and Its Implications For...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is now necessary to actively encourage fathers and male community members to help care for women and support their family in receiving adequate and improved healthcare. There is a positive correlation between male participation in family planning decisions and improved maternal and child health outcomes, according to a number of studies [ 80 , 81 ]. To achieve universal access to reproductive health care services, as part of the 2030 Agenda for Sustainable Development, it is crucial to increase access to contraception and ensure that the demand for FP is satisfied when utilizing effective contraceptive methods.…”
Section: Male Involvement In Family Planning and Its Implications For...mentioning
confidence: 99%
“…To achieve universal access to reproductive health care services, as part of the 2030 Agenda for Sustainable Development, it is crucial to increase access to contraception and ensure that the demand for FP is satisfied when utilizing effective contraceptive methods. Despite numerous coordinated efforts and success in increasing access to contraception, there are still significant obstacles to overcome [ 79 , 80 ]. Women’s empowerment, health, and gender equality are some of the related 17 SDGs goals/targets and the 2030 Agenda.…”
Section: Male Involvement In Family Planning and Its Implications For...mentioning
confidence: 99%
“…Evidence suggests that male partner involvement in family planning can help improve contraception uptake among women [ 10 , 15 ]. This is essential in reducing community-related stigma because in some cultures accessing contraception is regarded as a woman's responsibility [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The male's partner appreciation of FP services could go a long way to encourage female patronage of FP services. Mulatu et al [34] reported that male's involvement in discussions on FP, sexual and reproductive health, and approval from husbands on the use of FP were positive factors for FP use. On participants' attitudes towards male involvement in FP services, our study showed that most of the women had favourable attitudes towards males' involvement in FP services.…”
Section: Discussionmentioning
confidence: 99%
“…The male’s partner appreciation of FP services could go a long way to encourage female patronage of FP services. Mulatu et al [34] reported that male’s involvement in discussions on FP, sexual and reproductive health, and approval from husbands on the use of FP were positive factors for FP use.…”
Section: Discussionmentioning
confidence: 99%